2004
DOI: 10.37546/jaltjj26.2-2
|View full text |Cite
|
Sign up to set email alerts
|

Compliment-giving Behavior in American English and Japanese

Abstract: This study explores how the perceived likelihood of giving compliments differs between Americans and Japanese: that is, those who are said to belong to Brown & Levinson's positive politeness and negative politeness cultures, respectively. The results of the detailed analyses of a survey of 44 American and 44 Japanese university students suggest four major differences in compliment-giving behaviors. First, the distinction between uchi and soto affects Japanese compliment-giving behaviors, as Japanese tend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
(23 reference statements)
1
6
1
Order By: Relevance
“…The finding of this study is also in contradiction with Matsuura's (2004) study in which "American females indicated a significantly greater likelihood to give compliments than American males" (p. 164) while in the present study the reverse was true.…”
Section: The Role Of Gendercontrasting
confidence: 99%
See 1 more Smart Citation
“…The finding of this study is also in contradiction with Matsuura's (2004) study in which "American females indicated a significantly greater likelihood to give compliments than American males" (p. 164) while in the present study the reverse was true.…”
Section: The Role Of Gendercontrasting
confidence: 99%
“…Another factor that has affected the differences in the results of the two studies is that in Şakargil and Çubukçu's (2012) research, unlike the present study, features such as haircuts were not treated under the category of appearance, while we believe they should be. In fact, this is consistent with the views of other researchers in the field regarding items of appearance (see, e.g., Cordella, Large, & Pardo, 1995;Herbert, 1989;Manes & Wolfson, 1981;Matsuura, 2004;Sun, 2002;Wolfson, 1983).…”
Section: )supporting
confidence: 90%
“…In American culture giving compliments is generally considered a positive thing, and may range from appreciating someone's dress or the way one looks or even behaves. However in eastern cultures, it is perceived as negative politeness (Matsuura, ). Considering the concept as one of the core components of the programme, it was adapted to saying nice things to others where focus is more on the behaviours and acts of individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Although they are culture universals, researchers have found that these compliments tend to vary considerably in formulas, responses and topics according to societies' socio-cultural norms (Farghal & Al Khatib, 2001). With respect to the compliment topic, which is of concern to the current paper, Barnlund and Araki (1985) and Matsuura (2004) investigation of American and Japanese compliments shows that skill, work and study (i.e. achievement and ability) are the most frequently complimented attributes in Japan.…”
Section: Introductionmentioning
confidence: 86%